Abnormal current dependence of high-level reverse intersystem crossing induced by Dexter energy transfer from hole-transporting layer. Issue 32 (15th July 2020) - Tang, Xiantong; Pan, Ruiheng; Xu, Jing; Jia, Weiyao; Qu, Fenlan; Zhao, Xi; Xiong, Zuhong
Abstract : Extra Dexter energy transfer from hole-transporting layer can induce the abnormal current dependence of HL-RISC process in rubrene-doped OLEDs. Abstract : High-level reverse inter-system crossing (HL-RISC, T2, rub → S1, rub ) in rubrene molecules has been recently found as a potential evolution channel of excitons for realizing high-efficiency organic light-emitting diodes (OLEDs), and this channel usually presents a normal bias-current dependence. Here, an abnormal current ( I ) dependence of the HL-RISC process, which enhances with increasing I, is observed in rubrene-doped devices with low dopant concentration ( C ) of 1% and always exists from room temperature down to 20 K, but disappears as C increases up to 3%. By analyzing the energy level structures and I -dependent electroluminescent spectra of devices with different C, the extra Dexter energy transfer (DET) process from hole-transporting layer (HTL) to rubrene emitter enables the population of T2, rub states to increase with I, leading to the abnormal current dependence of HL-RISC. Additionally, this unusual phenomenon is independent of the changes of the host material or the electron-transporting layer but is closely associated with the HTL of the control devices (with C = 1%). This is because the energy level barrier at the HTL/host interface plays an important role for the occurrence of the extra DET process and the increase of T2, rub states. Undoubtedly, this work not only deepens the comprehensive understanding of the amazing HL-RISC channel in rubrene-based devices, but also provides ideas for designing reduced efficiency roll-off OLEDs at high bias currents.